2009
DOI: 10.1097/npt.0b013e3181b57de5
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill-Based Locomotor Training with Leg Weights to Enhance Functional Ambulation in People with Chronic Stroke: A Pilot Study

Abstract: This pilot study demonstrates that the combination of leg weights and treadmill training is a feasible approach, that is well tolerated by participants. This approach may have the potential to improve some aspects of functional ambulation and the performance of activities requiring hip and knee flexion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…(Laufer et al, 2001;Gorman, 2007;Lam et al, 2009). Randomized trials of BWSTT have shown improvements in gait parameters such as stride length and singlelimb support in the chronic stroke patients (Laufer et al, 2001;Werner et al, 2002).…”
Section: Body Weight Support Treadmill Trainingmentioning
confidence: 95%
See 1 more Smart Citation
“…(Laufer et al, 2001;Gorman, 2007;Lam et al, 2009). Randomized trials of BWSTT have shown improvements in gait parameters such as stride length and singlelimb support in the chronic stroke patients (Laufer et al, 2001;Werner et al, 2002).…”
Section: Body Weight Support Treadmill Trainingmentioning
confidence: 95%
“…In a hemiparetic patient, BWSTT creates a partial unloading of the lower extremities. Reduced load on the paretic lower extremity results in a straighter trunk and knee alignment during the weight bearing phase (Laufer et al, 2001;Lindquist et al, 2007;Lam et al, 2009). Further, due to movement of treadmill, there is a decrease in double-limb support time (stance phase), increase in single-limb support time (swing phase) and increase in walking speed (Laufer et al, 2001;Enzinger et al, 2009).…”
Section: Body Weight Support Treadmill Trainingmentioning
confidence: 97%
“…Given these functional considerations, it seems warranted to further investigate the potential benefits of gait training combined with resistance. In people with chronic stroke, we have shown that up to 12 wk of BWSTT combined with leg weights around the paretic limb could improve functional ambulation, including the ability to climb stairs [39]. A recent case report study of the effect of a 3 mo training study using Lokomat-applied resistance in an individual with chronic m-iSCI also showed very promising results [40].…”
Section: Introductionmentioning
confidence: 96%
“…A study by Lam et al 13 reported that additional weight application on stroke patients showed increased flexor strength during flexion of the lower limb in the swing phase of gait, and influenced activation of the extensor muscles during the stance phase of gait.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 These results show increasing capabilities with an increase in swing phase following hip joint flexor muscle activity increase. 13 However, studies mentioned above are cross-sectional studies and not training studies, which is inadequate to testify about aquatic gait training with additional weight load applied onto stroke patients. In addition, most studies have focused on orthopedic patients, the elderly population, and normal, healthy people and there is lack of research with detailed data on balance abilities of patients with central nervous system diseases.…”
Section: Introductionmentioning
confidence: 99%